2019
DOI: 10.5430/cns.v7n3p27
|View full text |Cite
|
Sign up to set email alerts
|

Effect of educational guidelines based on health belief model regarding testicular cancer knowledge, practice and beliefs among male nursing students

Abstract: Background: Testicular cancer is considered one of the most important health threats in a young men’s life. However, it is easily detected at an early stage by periodic testicular self-examination (TSE). Awareness of testicular cancer and TSE among university students is very important to aid in early detection and improve health belief. Aim: This study was conducted to evaluate the effect of educational guidelines based on health belief model regarding testicular cancer knowledge, practice and beliefs among m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 30 publications
1
17
0
1
Order By: Relevance
“…Como se muestra en el cuadro 2, todas creencias de salud para el cáncer y la autoexploración testicular, lo cual permite tener un instrumento para la evaluación e intervención sobre este comportamiento. Algunos estudios muestran que las intervenciones basadas en el modelo de creencias pueden ser efectivas en mejorar el conocimiento y la práctica de la AT y disminuir las barreras y mejorar la autoeficacia percibida; los resultados pueden mantenerse durante 3 a 6 meses (27)(28). Este estudio muestra algunas limitaciones como que la población tiene un nivel educativo alto y solo son de universidades públicas.…”
Section: Análisis De Consistencia Internaunclassified
“…Como se muestra en el cuadro 2, todas creencias de salud para el cáncer y la autoexploración testicular, lo cual permite tener un instrumento para la evaluación e intervención sobre este comportamiento. Algunos estudios muestran que las intervenciones basadas en el modelo de creencias pueden ser efectivas en mejorar el conocimiento y la práctica de la AT y disminuir las barreras y mejorar la autoeficacia percibida; los resultados pueden mantenerse durante 3 a 6 meses (27)(28). Este estudio muestra algunas limitaciones como que la población tiene un nivel educativo alto y solo son de universidades públicas.…”
Section: Análisis De Consistencia Internaunclassified
“…Nursing students are an important population to study as they are the future healthcare providers who will be responsible for educating patients about self-examination practices and promoting preventative health behaviours (Avci and Altinel, 2018;El Mezayen and Abd El-Hay, 2019;Ustundag, 2019). However, studies have shown that nursing students also lack knowledge and awareness of TC and TSE (Ahmed et al, 2019;El Mezayen and Abd El-Hay, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Nursing students are an important population to study as they are the future healthcare providers who will be responsible for educating patients about self-examination practices and promoting preventative health behaviours (Avci and Altinel, 2018;El Mezayen and Abd El-Hay, 2019;Ustundag, 2019). However, studies have shown that nursing students also lack knowledge and awareness of TC and TSE (Ahmed et al, 2019;El Mezayen and Abd El-Hay, 2019). A study conducted in Saudi Arabia revealed that nursing students had poor knowledge and incorrect beliefs about TC and TSE, and this lack of knowledge was identified as a significant barrier to providing effective patient education (Alamri et al, 2021;Salati et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations